Identifying extra pulmonary vein targets for persistent atrial fibrillation ablation: bridging advanced and conventional mapping techniques - Sharp, Alexander J; Pope, Michael T; Briosa e Gala, Andre; Varini, Richard; Banerjee, Abhirup; Betts, Timothy R (Europace (London, England), 2025)
Abstract Aims Advanced technologies such as charge density mapping (CDM) show promise in guiding adjuvant ablation in patients with persistent atrial fibrillation (AF); however, their limited availability restricts widespread adoption. We sought to determine whether regions of the left atrium containing CDM-identified pivoting and rotational propagation patterns during AF could also be reliably identified using more conventional contact mapping techniques. Methods and results Twenty-two patients undergoing de novo ablation of persistent AF underwent both CDM and electroanatomic voltage mapping during AF and sinus rhythm with multiple pacing protocols. Through the use of a left atrium statistical shape model, the location of distinctive propagation patterns identified by CDM was compared with low-voltage areas (LVAs) and regions of slow conduction velocity (CV). Neither LVA nor CV mapping during paced rhythms reliably identified regions containing CDM propagation patterns. Conduction velocity mapping during AF did correlate with these regions (ρ = −0.63, P < 0.0001 for pivoting patterns; ρ = −0.54, P < 0.0001 for rotational patterns). These propagation patterns consistently occurred in two specific anatomical regions across patients: the anteroseptal and inferoposterior walls of the left atrium. Conclusion Mapping techniques during paced rhythms do not reliably correspond with regions of CDM-identified propagation patterns in persistent AF. However, these propagation patterns are consistently observed in two specific anatomical regions, suggesting a predisposition to abnormal electrophysiological properties. While further research is needed, these regions may serve as promising targets for empirical ablation, potentially reducing the reliance on complex mapping techniques. Graphical Abstract Graphical Abstract